2003
DOI: 10.2135/cropsci2003.2234
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding and Validation of Quantitative Trait Locus (QTL) Alleles Determining Resistance to Barley Stripe Rust

Abstract: The use of molecular and quantitative trait locus (QTL) analysis tools initially lent support to the idea that relatively few genetic factors were the principal determinants of complex traits, including quantitative resistance (QR) to plant diseases. However, there are concerns regarding bias in QTL estimation and reproducibility of QTL effects in different genetic backgrounds. We are interested in mapping determinants of QR, and pyramiding resistance alleles at QTL loci may lead to durable resistance as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…As reviewed by St.Clair (2010), there are successful examples of pyramiding QTL alleles for increased disease resistance in crop plants, including resistance to common bacterial blight in bean (Mutlu et al 2005), Fusarium head blight in wheat (Wilde et al 2008), root rot and shoot blight in pepper (Thabius et al 2004), and stripe rust in barley (Toojinda et al 1998; Castro et al 2003; Richardson et al 2006). Previously, Brouwer and St.Clair (2004) observed that pyramiding QTL lb5b and lb11b (contained in the NIL parents of our sub-NIL populations) resulted in a higher level of P. infestans resistance (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by St.Clair (2010), there are successful examples of pyramiding QTL alleles for increased disease resistance in crop plants, including resistance to common bacterial blight in bean (Mutlu et al 2005), Fusarium head blight in wheat (Wilde et al 2008), root rot and shoot blight in pepper (Thabius et al 2004), and stripe rust in barley (Toojinda et al 1998; Castro et al 2003; Richardson et al 2006). Previously, Brouwer and St.Clair (2004) observed that pyramiding QTL lb5b and lb11b (contained in the NIL parents of our sub-NIL populations) resulted in a higher level of P. infestans resistance (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…QTL validation for different rust diseases caused by Puccinia sp. has been carried out in wheat (Khlestkina et al 2007;Schnurbusch et al 2004), barley (Castro et al 2003), and sugar cane (McIntyre et al 2005) to name a few. In all cases a major locus conferring resistance to the rust disease was found and its presence validated across unrelated pedigrees.…”
Section: Discussionmentioning
confidence: 99%
“…vt-1BL explained proportionally less when compared to the values reported in the original BM mapping population (Liu et al 2001). Castro et al (2003) evaluated three QTL for APR to barley (Hordeum vulgare) stripe rust (Puccinia striiformis) in different genetic backgrounds and found that one QTL with a small genetic effect in the mapping population explained significantly more of the variation in a different genetic background. Therefore, it is likely that effects of QTL governing APR to powdery mildew will vary in different genetic backgrounds due to both positive and negative epistasis among genes affecting host resistance and susceptibility.…”
Section: Discussionmentioning
confidence: 99%